Revitalization of Kali Unda Tourism Objects - Nataprawira, Muhammad Rafli Ramdhani; Yudha, I Made Bendi; Gulendra, I Wayan (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
Paksebali Village is one of 12 villages in Dawan District and is located east of Semarapura City, 1 Km away. Paksebali Village consists of 5 Office Banjars. The Klungkung River Dam Tourism Object, which is currently called the Unda River Tourism Object, is the most easily accessible tourist attraction because when heading to this area it is located close to the connecting bridge between Klungkung City and Dawan District. The Kali Unda Tourism Object has a natural panorama that captivates tourists because this tourist spot has a dam that forms a two-story waterfall, which is known as "Curtain Waterfall". Around the dam there are shady trees and restaurant huts as a means of enjoying the natural beauty of Kali Unda Tourism Object. Revitalizing the Unda River Tourism Object through Community Service activities, the condition of the Unda River is currently increasingly apprehensive, namely environmental conditions that are not maintained, lack of reflection therapy fish ponds, ornamental fish ponds and fish nurseries, botanical gardens, and inadequate photo spots. Likewise with existing infrastructure such as changing room walls, mossy and dull toilets, no signs providing information, and unused entry counters, so revitalization is needed to restore and increase visits as a water tourism object.